Project Report on Autonomous Color Segregating Pick and Place Robot - NAVEEN S, RAGHAVENDRA. SACHIN RAJ and SHIVAMURTHY (2012)
INTERNAL GUIDE: APARNA P, ECE DEPT, MVJCE
Keywords: Autonomous Color Segregating Pick and Place Robot